Cover Picture: Liquid Chromatography Mass Spectrometry Study of a Eutectic Mixture of bis(2, 2‐Dinitropropyl) Acetal/Formal (Prop., Explos., Pyrotech. 12/2021). Issue 12 (3rd December 2021) - Wong, Camille Hing; Edgar, Alexander Steven; Yang, Dali
Abstract : The cover image is based on the Research Article Liquid Chromatography Mass Spectrometry Study of a Eutectic Mixture of bis(2, 2‐Dinitropropyl) Acetal/Formal by Camille Hing Wong et al., https://doi.org/10.1002/prep.202100189 . The Research Article can be found on page 1849 ff.